Analysis Of Agrarian Conflict 2023 On Rempang Island Riau Islands In Laswellian Perseptive - Hayatun Nufus; Jamalullail Jamalullail; Mira Natalia Pellu; Marwan Hadi; Wahyu Adi Setyo Wibowo (Jurnal Mamangan, 2023)
The agrarian conflict on Rempang Island, Riau Archipelago Province, reflects structural issues involving indigenous communities, the government, and investors in the context of the Rempang Eco-City development. This study analyzes the conflict using Harold Lasswell's (1936) political communication perspective on "Who Gets What, When, and How?" and Jürgen Habermas's (1991) concept of the public sphere to understand the lack of deliberative communication that includes all parties." This conflict was triggered by the granting of Business Use Rights (HGU) without transparency in the early 2000s, leading to physical clashes in September 2023. This research uses a descriptive-analytical qualitative method, with data collection techniques through literature studies on relevant regulations and data. Results show that deliberative dialogue based on respect for customary rights is key to sustainable agrarian conflict resolution. Clashes between security forces and the community occurred on September 7, 2023, marking the peak of the tension that had built up. How? The resolution of this conflict ideally involves a dialogic communication approach that embraces and prioritizes the community's rights. However, errors in land rights documentation by the central and regional governments have become one of the factors causing this conflict. The Riau Islands provincial and national governments are expected to adopt consistent spatial planning policies that are human rights-sensitive, with mass communication and constructive dialogue with communities and potential investors/developers. The key is cultural communication that penetrates indigenous communities and Malay culture. The research findings indicate a contradiction between the ideal development policies ratified by the national government and the protection of the traditional rights of indigenous communities that are neglected in the region. This research also highlights the importance of legal recognition of the rights of indigenous peoples on Rempang Island as part of the state's responsibility to respect and protect the implementation of the International Covenant on Economic, Social, and Cultural Rights (ICESCR) ratified by the Republic of Indonesia through Law Number 11 of 2005.